Audit of Caesarean section Documentation - Jahan Ara Saeed (Journal of Rawalpindi Medical College, 2016)
Background: To study the standard of caesarean section surgical documentation Methods : In this retrospective study 30 consecutive cases who underwent cesarean section were studied. The surgical documentation was analyzed on 16 parameters under three major categories. Category 1 was regarding the personnel. This included the documentation of name of surgeon, assistant and anesthetist. Category 2 was surgical procedure giving detail about Status of uterine cavity, skin and uterine incision, uterine and skin closure, Venous thrombosis risk , blood loss and finally the instrument count, swab count and post op plan. Category 3 was regarding the baby gender , weight, Apgar score and cord pH. Results: There were deficiencies in the surgical detail documentation of caesarean section .The documentation of personnel was 95%.The surgical documentation regarding uterine cavity and blood loss during surgery were 90%.Documentation regarding swab and instrument count being complete was only in 25% of the cases. Post op plan was documented in only 60% of the cases. Notes regarding the newborn were insufficient. The documentation of baby gender, weight and Apgar score were 85%, 45% and 65% respectively. Conclusion: Caesarean section surgical documentation needs to meet international standard of minimal documentation. It is required to introduce a minimal standard surgical document to be attached in the notes of all patients undergoing caesarean section to be completed by the operating surgeon within 24 hrs of surgery.